Boundaries updated and expanded edition eaudiobook When to say yes, how to say no to take control of your life. - Cloud, Henry (Zondervan, 2018)
Join the millions who have learned how to take control of their lives by setting healthy boundaries with their spouses, children, friends, parents, coworkers, and even themselves, in order to live life to the fullest. Do you feel like your life has spiraled out of control? Have you focused so much on being loving and unselfish that you've forgotten your own limits? Do you find yourself taking responsibility for other people's feelings and problems? In Boundaries, Drs. Henry Cloud and John Townsend teach you the ins and outs of setting the boundaries that will transform your daily life. Boundaries, a New York Times bestseller, will give you the tools you need to learn to say yes and know how to say no. Drs. Henry Cloud and John Townsend are here to share the lessons they've learned in their years of practicing psychology and studying the patterns and practices that support clear biblical boundaries. Since it was first published, Boundaries has supported millions of people around the world as they discover the importance of understanding their limitations and upholding their boundaries. In this updated and expanded edition of Boundaries, Drs. Cloud and Townsend answer the most common questions they've received in more than thirty years that they've studied the science behind establishing boundaries: Can I set limits and still be a loving person? What are legitimate boundaries? How do I effectively manage my digital life so that it doesn't control me? What if someone is upset or hurt by my boundaries? How do I answer someone who wants my time, love, energy, or money? Why do I feel guilty or afraid when I consider setting boundaries? How do boundaries relate to mutual submission within marriage? Aren't boundaries selfish? Discover the countless ways that Boundaries can change your life for the better today!